Analysis Of The Physical Condition Of Futsal Athletes Min 03 Muko-Muko - Aziz, Abdul; Martiani, Martiani; Sumantri, Ajis (Jurnal Pendidikan Rafflesia, 2024)
Futsal is a sport favoured by everyone that requires speed endurance, strength endurance, and agility in a relatively long time. This study aims to determine the physical condition of MIN 03 Muko-Muko athletes. The components measured are physical condition components namely speed, agility, leg power and aerobic endurance. This research method is a descriptive method with data collection techniques in the form of tests and measurements. The sample of this study was 10 MIN 03 Muko-Muko futsal athletes. The instrument used is speed measured by a 30-meter running test in seconds, agility measured using the Illinois agility run test with units of seconds, leg power measured using a vertical jump test in cm units and aerobic endurance measured using a multi-stage test (multi stage test) with units of ml / kg / min, then all data is converted into T - score. The results showed that the physical condition of MIN 03 Muko-muko futsal athletes based on T-Score was in the good category with a percentage of 40% (4 people), moderate category with a percentage of 40% (4 people), poor category with a percentage of 10% (1 person) and very poor category with a percentage of 10% (1 person). While based on the average of 200, the physical condition of MIN 03 Muko-Muko futsal athletes is in the moderate category.